Bias in quantification of light absorption enhancement of black carbon aerosol coated with low-volatility brown carbon. Issue 5 (25th March 2021) - Shetty, Nishit; Beeler, Payton; Paik, Theodore; Brechtel, Fred J.; Chakrabarty, Rajan K.
Abstract: Brown carbon (BrC) is an optically defined class of organic carbon (OC) which strongly absorbs light at shorter visible and ultraviolet-A (UVA) wavelengths. Both light absorbing and non-absorbing OC have been found to coat black carbon (BC) and could modulate the optical properties of BC. Thermodenuders are conventionally used in conjunction with instruments measuring particle light absorption, such as photoacoustic spectrometers, to parametrize enhanced BC light absorption (Eabs ) due to OC. This method can introduce unquantified measurement artifacts because thermodenuders do not remove low-volatility compounds at the temperatures they are commonly operated at and due to temperature-dependent loss of particles within the instrument. These artifacts could lead to errors in accurately estimating Eabs for coated BC particles. The value of Eabs can also be estimated by comparing the mass absorption cross-section (MAC) of coated BC aerosol to literature-based MAC values of uncoated BC. In this study, we use two integrated photoacoustic-nephelometer spectrometers, operating at wavelengths of 375 nm and 532 nm, respectively, to quantify the differences and errors associated with measuring Eabs using these two methods. Our results indicate differences ranging from 25% to 65% for Eabs measured using both methods at 375 nm. We observed little to no enhancement at either wavelength using the thermodenuder method. In contrast, the Eabs value increased with the OC/BC ratio at 375 nm using the literature-based MAC method. The difference between the two methods was attributed to the presence of low-volatility brown carbon, and these results were corroborated using discrete dipole approximation calculations. Theoretical calculations predicted that these low-volatility OC could have values of the imaginary part of the refractive index up to 0.32 at a wavelength of 375 nm, which is in line with previous studies that found large absorption by low-volatility organics. Copyright © 2021 American Association for Aerosol Research